Perceptions of a Glass Ceiling at Top Management Positions in Croatian Organizations - Ivana Martinčević; Mirjana Pejić Bach; Igor Klopotan (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
Being successful and competitive in the market today is the challenge of every business. Successfully managing and leading a company to set goals is one of the key tasks of company management. The manager is the one who needs to know fully and understand the functioning of the business system of the company and be able to respond to market challenges. Whether a manager is a man or a woman, he or she needs the have skills, knowledge needed to manage a business. People, their intellectual capital, abilities, and competencies are the key to effective management and management of a company regardless of gender. In today's business environment and the managerial world, men are those who dominate in higher (leading) management positions, and women managers have difficulty to advance into higher and leading managerial positions. Various prejudices and discrimination are visible in the area of involvement of women in higher hierarchical managerial positions, so their progress and piercing are difficult. For this reason, we can talk about the existence of phenomena of so-called "Glass ceiling”. Glass ceiling in the economic sense refers to the invisible "ceiling", referring to the barrier encountered by women who want to move to higher managerial positions. In the Republic of Croatia, there is still a gap and prejudice while on the global level, more and more companies recognize the importance of women's involvement in company management and higher managerial positions.
Keywords: M10; M12; 330; management; managerial positions; man in management; women in management; glass ceiling phenomen